Affibody-functionalized Ag2S quantum dots for photoacoustic imaging of epidermal growth factor receptor overexpressed tumors - Zhang, Ying; Zhao, Ning; Qin, Yeshan; Wu, Fengxia; Xu, Zhihua; Tian Lan; Cheng, Zhen; Zhao, Ping; Liu, Hongguang (Nanoscale, 2018)
Photoacoustic imaging (PAI) is a new and attractive imaging modality, and it has strong potential for application in the early detection of tumors through the use of optically absorbing targeted contrast agents. Ag2S quantum dots (QD) are a promising bionanomaterial and have attracted significant attention in the field of bioimaging. In this study, water-soluble and carboxylic acid group-coated Ag2S QDs with an ultrasmall size (∼8 nm) were synthesized via a one-step method. Their surface plasmon resonance wavelength was determined to be ∼800 nm, which is ideal for PAI. Ag2S QDs were then modified with the epidermal growth factor receptor 1 (EGFR) targeted small protein affibody ZEGFR:1907. The resulted nanoprobe, ZEGFR:1907-Ag2S QDs, was then used for targeted PAI of EGFR-overexpressed tumors. The biodistribution of the nanoprobe was further measured by ex vivo near infrared fluorescence (NIRF) imaging of the dissected tissues. The PAI results showed that ZEGFR:1907-Ag2S QDs specifically image EGFR positive tumors. The biodistribution study revealed that the nanoprobe mainly accumulated in the liver, spleen and tumors; tissue H&E staining studies indicated that the probe has good biocompatibility. Overall, the affibody-functionalized Ag2S QDs are a novel targeted nanoprobe that can be used for specific PAI of tumors.